2018
DOI: 10.1016/j.chemosphere.2017.08.167
|View full text |Cite
|
Sign up to set email alerts
|

The use of toxicokinetics and exposure studies to show that carprofen in cattle tissue could lead to secondary toxicity and death in wild vultures

Abstract: Veterinary medicines can be extremely damaging to the environment, as seen with the catastrophic declines in Gyps vulture in South Asia due to their secondary exposure to diclofenac in their primary food source. Not surprisingly, concern has been raised over other similar drugs. In this study, we evaluate the toxicity of carprofen to the Gyps vulture clade through plasma pharmacokinetics evaluations in Bos taurus cattle (their food source) and Gyps africanus (a validated model species); tissue residues in catt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 23 publications
2
36
0
Order By: Relevance
“…This incidence raises concern on the vulnerability of the Accipitriformes and other raptors to diclofenac toxicity. Complications due to the toxic consequences of diclofenac have also been reported in the Cape vulture ( Swan et al, 2006b ; Naidoo et al, 2009 ; Naidoo et al, 2010 ; Naidoo et al, 2018 ; Adawaren et al, 2018 ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…This incidence raises concern on the vulnerability of the Accipitriformes and other raptors to diclofenac toxicity. Complications due to the toxic consequences of diclofenac have also been reported in the Cape vulture ( Swan et al, 2006b ; Naidoo et al, 2009 ; Naidoo et al, 2010 ; Naidoo et al, 2018 ; Adawaren et al, 2018 ).…”
Section: Introductionmentioning
confidence: 97%
“…Raptors are valuable indicators of habitat quality based on their ecological sensitivity as predators and scavengers ( Lerner & Mindell, 2005 ). However, vultures belonging to the Accipitriformes order are currently facing devastating drops in their population numbers from an array of problems ranging from loss of their natural habitat, collision with high-tension electric cables and wind turbines, intentional poisoning of animal carcasses by poachers of endangered wildlife species and accidental ingestion of carcasses contaminated with pharmaceuticals ( Ogada et al, 2016 ; Naidoo et al, 2018 ; Adawaren et al, 2018 ). One notable incident was the near complete extinction of three Gyps vulture species the white-rumped vulture ( Gyps bengalenesis ), the Indian vulture ( G. indicus ) and the slender-billed vulture ( G. tenuirostris ) in India, Nepal and Pakistan from the consumption of carcasses of animals dosed with diclofenac ( Oaks et al, 2004 ; Swan et al, 2006b ; Naidoo et al, 2009 ; Adawaren et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the European Union (EU) a few NSAIDs are au-thorized for dairy cows with established maximum residues limits (MRLs) in milk: Tolfenamic acid (TLF) -50 µg/kg; flunixin (FLU) (marker residue 5-hydroxyflunixin) -40 µg/kg; meloxicam (MLX) -15 µg/ kg; metamizole (marker residue 4-methylaminoantipyrine (4MMA)) -50 µg/kg; and diclofenac (DCL) with very low MRL of 0.1 µg/kg [5]. Carprofen (CPF) is licensed for use in dairy cattle and has no required MRL in bovine milk; the target value for the analytical method was set at 500 µg/kg for our in-house monitoring of the substance, due to occurrence of vultures' death from consuming livestock carcasses [6]. Ibuprofen (IBU) and phenylbutazone (PBZ) are non-authorized for veterinary use in food-producing animals and have no established MRLs in milk; IBU and PBZ should be analyzed (as defined in CRL Guidance Paper of 2007 [7]) at the recommended concentrations (RC) of: 10 µg/kg and 5 µg/kg, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, safety trials have now confirmed nephrotoxicity at plausible field exposure levels in Gyps due to ketoprofen [33], carprofen [34] and aceclofenac [35] -whilst very worryingly, both nimesulide (in South Asia; [36] and flunixin (in Europe; [37]) have now been clearly linked to wild Gyps mortalities on two continents. Further, concern now also exists regarding potential impacts on what some may consider to be more enigmatic species such as eagles, following the death of two steppe eagles (Aquila nipalensis) in India in association…”
Section: Accepted Manuscriptmentioning
confidence: 99%